Calf stretch effectiveness in plantar fasciitis cases: A case series - Andre Triadi Desnantyo; Dimas Aditya Wahyu (Universitas Muhammadiyah Surabaya, 2024)
Plantar fasciitis in Indonesia, occur after 30 years of age, 77% of sufferers between 40 to 69 years old, men to women is 1:2. There are risk factors for plantar fasciitis include structural abnormalities, being overweight, age-related degenerative changes, activities that require prolonged standing and/or ambulation, and errors in training, especially in athletes. We present 20 case series of all patients diagnosed with plantar fasciitis who went to the Orthopedic Polyclinic in 2018 and 2019, they received conservative management with Calf Stretch workouts for 30 days and were evaluated with AOFAS Score. Calf stretch exercises in which the patient stands with the sore leg behind and both hands pushing against a wall, also known as the wall stretch. This exercise is performed 2 times a day with a duration of 10-15 minutes each session. This exercise is done routinely for 30 days. A simple, progressive training protocol consisting of strength training with heavy weights will produce better results in the first three months when compared to plantar-focused stretching and may aid in more rapid relief of symptoms on pain. Conservative management with calf exercises still provides a good outcome in patients with plantar fasciitis, based on the AOFAS score.